Growth performance of Hydrangea macrophylla ‘glowing embers’ on culture medium with different macro-element concentrations and culture conditions - Luc, Thi The; Minh, Nguyen Le Thu; Quynh, Nguyen Thi (Academia Journal of Biology, 2020)
Hydrangeas are very popular shrubs thanks to their attractive, colorful flowers and foliage. Recently, they have been commercialized for cut-flower production. For mass propagation of this plant species using plant tissue culture, it is necessary to study the effects of culture medium and culture conditions on in vitro plant growth. In the first experiment, in vitro hydrangea shoots were cultured for 56 days on Murashige and Skoog (MS) media containing one among five different types of macro-elements. The half concentration of NH4NO3 on MS macro-elements significantly increased fresh and dry weights of hydrangea shoots in comparison with other treatments. The number of roots of in vitro plants in this treatment were the highest, resulting in better absorption of culture nutrient. Cross sections of the shoot base on day 14th showed that reducing only NH4NO3 on the MS medium enhanced the formation of adventitious roots. The experiment on culture conditions showed that photoautotrophic condition was suitable for the in vitro growth of hydrangea. Plants grown under photoautotrophic (PA) condition had increased fresh weight (341.39 mg/plt), increased dry weight (31.03 mg/plt) with leaf area (7.76 cm2) significantly greater than those grown under photomixotrophic (PM) condition (259.53 mg/plt, 38.22 mg/plt and 4.73 cm2 respectively). In addition, the net photosynthetic rate (Pn) of plants under PA condition was statistically higher and increased over the culture period while Pn of plants under PM condition remained constant. This study demonstrated that MS salts with half concentration of NH4NO3 and photoautotrophic culture method were appropriate for in vitro growth of hydrangea.